Neonatal Hypopituitarism: Unusual Presentation - Abu-Libdeh, Abdulsalam; Abu-Libdeh, Bassam; Abdulhag, Ulla Najwa (Journal of Child Science, 2017)
Objective We report an infant with panhypopituitarism presenting with cholestatic jaundice, hypoglycemia, and high ferritin level.Methods We conducted clinical and laboratory investigations, including metabolic, infectious, and hormonal evaluation.Results Hormonal evaluation revealed panhypopituitarism (cortisol deficiency, growth hormone deficiency, and central hypothyroidism). Other causes of cholestasis were ruled out. Surprisingly, serum ferritin level was very high suggesting neonatal hemochromatosis, which was ruled out by the absence of hemosiderin deposition in buccal mucosal biopsy. Replacement therapy with glucocorticoids and L-thyroxin showed improvement of liver function tests, resolved cholestatic jaundice, and significantly decreased serum ferritin level. These findings support the assumption that thyroid hormone and cortisol affect the bile acid-independent bile flow.Conclusion This is the first description of an infant with congenital panhypopituitarism, presenting with cholestasis, hypoglycemia, and high serum ferritin level. Panhypopituitarism should be considered in any infant who presents with cholestasis, hypoglycemia, and other manifestations of pituitary malfunction. High serum ferritin level probably reflects acute phase reaction.
Keywords: cholestasis; panhypopituitarism; hemochromatosis